2018
DOI: 10.1017/s0007114518003598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of daily 10–85 μg vitamin D supplements during pregnancy and lactation on maternal vitamin D status and mature milk antirachitic activity

Abstract: Pregnant and lactating women and breastfed infants are at risk of vitamin D deficiency. The supplemental vitamin D dose that optimises maternal vitamin D status and breast milk antirachitic activity (ARA) is unclear. Healthy pregnant women were randomised to 10 (n 10), 35 (n 11), 60 (n 11) and 85 (n 11) µg vitamin D3/d from 20 gestational weeks (GW) to 4 weeks postpartum (PP). The participants also received increasing dosages of fish oil supplements and a multivitamin. Treatment allocation was not blinded. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…An analysis of the studies who specifically looked into the relationship between vitamin D supplementation and vitamin D concentration in breast milk was conducted. A total of 10 trials [ 26 , 27 , 31 , 32 , 35 , 37 , 40 43 ] investigated the effect of vitamin D supplementation on breast milk concentration. All studies, except one [ 40 ], concluded that vitamin D supplementation could significantly increase vitamin D concentration in breast milk.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the studies who specifically looked into the relationship between vitamin D supplementation and vitamin D concentration in breast milk was conducted. A total of 10 trials [ 26 , 27 , 31 , 32 , 35 , 37 , 40 43 ] investigated the effect of vitamin D supplementation on breast milk concentration. All studies, except one [ 40 ], concluded that vitamin D supplementation could significantly increase vitamin D concentration in breast milk.…”
Section: Resultsmentioning
confidence: 99%
“…At 36 weeks, only with doses of 1400 IU/day did 97.5% of women present with an adequate status. No adverse effects or signs of vitamin D toxicity were reported [29].…”
Section: Discussionmentioning
confidence: 97%
“…Considering that the compliance with daily VD supplementation in the first years of life is variable in different countries, and that rates of withdrawal and adherence change during the first months of life, an increased awareness about the correct posology and doses of VD administration is needed [ 22 , 23 , 24 ]. The main factors affecting VD levels in infants are related to the mother’s serum concentrations during pregnancy and lactation, the length of sun exposure of the child and the total intake assumed by diet or supplementation [ 75 , 76 , 77 ]. While fish, lipids and dairy products are the main sources of VD for humans, breast milk is a limited source of this micronutrient [ 1 , 78 ].…”
Section: Discussionmentioning
confidence: 99%